2001
DOI: 10.1046/j.0014-2956.2001.02535.x
|View full text |Cite
|
Sign up to set email alerts
|

SCCA2 inhibits TNF‐mediated apoptosis in transfected HeLa cells.

Abstract: Abbreviations: SCCA1, squamous cell carcinoma antigen 1; SCCA2, squamous cell carcinoma antigen 2; TNF, tumour necrosis factor-alpha; RCL, reactive centre loop; PI-9, proteinase inhibitor 9; PAI 2, plasminogen activator inhibitor 2; crmA, cytokine response modifier A; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide; succ-AAPF-pNA, succinyl-Ala-Ala-Pro-Phep-nitroanilide; Ac-DEVD-amc, acetyl-Asp-Glu-Val-Asp7-amido-4-methylcoumarin.Eur. J. Biochem. 268, 5868-5875 (2001) q FEBS 2001 protects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 32 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…For example, the inhibition of cathepsins has been described by the human serpins SCCA 1 and 2 and the mouse serpin SQN-5 [23,24]. Furthermore, overexpression of SCCA2 protected HeLa cells from TNF-a-mediated PCD [25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inhibition of cathepsins has been described by the human serpins SCCA 1 and 2 and the mouse serpin SQN-5 [23,24]. Furthermore, overexpression of SCCA2 protected HeLa cells from TNF-a-mediated PCD [25].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the location of action, some serpins act on the cell surface. For example, PAI-2 and SCCA-2 are involved in the inhibition of TNF-mediated apoptosis through cell surface interaction (Dickinson et al, 1998;McGettrick et al, 2001). Other serpins act to inhibit intracellular proteases such as granzyme B and caspases Bird et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, SCC antigen-1 inactivated cysteine proteinases, e.g., papain, cathepsins, L, S, K, and L2, as well as chymotrypsin, a serine proteinase [11][12][13][14], while SCC antigen-2 inactivates serine proteinases, e.g., cathepsin G and mast cell chymase [15]. As for the biological significance of the proteinase inhibitor activity of SCC antigens, more recently, McGettrick et al [16] reported that SCC antigen-2 attenuated tumor necrosis factor a (TNFa)-mediated apoptosis in HeLa cells by inhibiting TNFa-induced cathepsin G. However, there is no evidence of the interaction of native SCC antigen-1 with specific endogenous proteinases in vivo. When a native serpin such as plasminogen activator inhibitor-2 (PAI-2) interacts with an endogenous target proteinase, the specific cleavage of the serpin within its RCL leads to the formation of the cleaved and thermodynamically more stable conformation [17].…”
Section: Introductionmentioning
confidence: 98%